Long non‐coding RNA SNHG16 has Tumor suppressing effect in acute lymphoblastic leukemia by inverse interaction on hsa‐miR‐124‐3p. Issue 1 (31st October 2018) - Yang, Tianxin; Jin, Xing; Lan, Jianping; Wang, Wensong
Abstract: Acute lymphoblastic leukemia (ALL) is one of the deadly forms of childhood cancers in the world. In the present study, we used both in vitro and in vivo models to evaluate the functional mechanisms of a long noncoding RNA (lncRNA), small nucleolar RNA host gene 16 (SNHG16) in ALL. SNHG16 gene expression was evaluated by quantitative real‐time PCR (qPCR) in both in vitro ALL cell lines and in vivo human samples of T lymphocytes. Lentivirus‐mediated SNHG16 downregulation was performed in MOLT3 and SUP‐B15 cells, to evaluate its functional effects on ALL cell proliferation, migration in vitro, and ALL transplant in vivo. Epigenetic regulation of SNHG16 on human miR‐124‐3p (hsa‐miR‐124‐3p) was evaluated by dual‐luciferase activity assay and qPCR. Hsa‐miR‐124‐3p was inhibited in SNHG16‐downregulated MOLT3 and SUP‐B15 cells to further evaluate the functional correlation between SNHG16 and hsa‐miR‐124‐3p in ALL. SNHG16 is upregulated in both in vitro ALL cell lines and in vivo human leukemic T‐cells. SNHG16 downregulation suppressed ALL proliferation and migration in vitro, and ALL explant in vivo. Hsa‐miR‐124‐3p was demonstrated to interact with SNHG16, and upregulated in SNHG16‐downregulated ALL cells. In addition, inhibiting hsa‐miR‐124‐3p reversed SNHG16‐downregulation‐mediated tumor suppressive functions in ALL. SNHG16 is upregulated in ALL, and its inhibition has tumor suppressive effect in ALL, likely through epigenetic interaction on hsa‐miR‐124‐3p. © 2018 IUBMB Life, 71(1):134–142, 2019